Large wood load and transport in a flood‐free period within an inter‐dam reach: a decade of monitoring the Dyje River, Czech Republic. Issue 14 (3rd September 2020) - Máčka, Zdeněk; Kinc, Ondřej; Hlavňa, Matej; Hortvík, David; Krejčí, Lukáš; Matulová, Jana; Coufal, Pavel; Zahradníček, Pavel
Abstract: This study examined the large wood (LW) load and transport during the non‐flood period (2009–2018) following major floods that occurred in 2002 and 2006 within the inter‐dam reach of the Dyje River (Czech–Austrian border). The LW load was examined in 36 river corridor segments scattered within the reach in the 2009–2018 period. Two whole‐reach surveys (2011 and 2019) on LW frequency and distribution were conducted, and the export of LW to the downstream reservoir was analysed between June 2013 and December 2018. In the period of non‐flood discharges, the recruitment and depletion of LW were highly variable processes in space and time, leading to a considerable change in the total LW quantity. Whereas the total number of LW pieces decreased, the total LW volume increased because of the increasing dimensions of newly recruited pieces. The annual variability in the quantity of newly recruited pieces was better explained by the variation in the maximum annual discharges ( y = 41.043ln( x ) + 3.2737, R 2 = 0.5352) than by the variability in the number of days with wind gusts >17.2 m/s ( y = 1.5004 x + 82.096, R 2 = 0.118). The land use change with the abandonment of human settlements after World War II and the progressive expansion of forest was the major historical factor driving the increased recruitment of LW to the river corridor. While the 2006 (>100‐year RI) flood brought approximately 1, 250 LW pieces to the reservoir, the 2013 (1.5‐year RI) flood delivered 45 pieces. The long‐term average monthly input of LW to the reservoir was 7.7 pieces. The exceptional low‐magnitude flood of 2013, which occurred at the beginning of the monitoring period, was shown to be a threshold above which the number of LW pieces that floated to the dam significantly increased. © 2020 John Wiley & Sons, Ltd. Abstract : Large wood (LW) load was investigated in the 36 river corridor segments within the inter‐dam reach of the Dyje River in the non‐flood period 2009–2018 following three major floods. Tagging of LW in 36 river corridor segments together with documenting LW floated to the downstream dam revealed the spatiotemporal pattern of LW recruitment, transport and depletion. A mean export of 7.7 LW pieces per month was recorded in the 2013–2018 period lacking discharges exceeding bankfull stage.